Effects of Supplementing Rumen-Protected Methionine and Lysine on Milk Performance and Oxidative Status of Dairy Ewes - Alexandros Mavrommatis; Christina Mitsiopoulou; Christos Christodoulou; Paraskevi Kariampa; Marica Simoni; Federico Righi; Eleni Tsiplakou (MDPI AG, 2021)
There is limited information on the impact of dietary supplementation with separate rumen-protected (RP) amino acids (AA), or with their combination, on ewes' oxidative status. Sixty ewes were divided into five groups; C: basal diet (control); M: basal diet + 6 g/ewe RP methionine; L: basal diet + 5 g/ewe RP lysine; LML: basal diet + 6 g methionine and 5 g lysine/ewe; and HML: basal diet + 12 g methionine + 5 g lysine/ewe. Milk's fat content increased in RP-AA fed ewes, while that of protein in M and L only. In blood plasma, the malondialdehyde (MDA) content was reduced in the M, LML, and HML compared to C-fed ewes. An increase in glutathione transferase activity in the blood plasma of the M and LML compared to the C and HML-fed ewes were found. In milk, lower values of the ferric reducing ability of plasma (FRAP) in the LML and HML-fed ewes and of 2,2'-Azino-bis 3-ethylbenzthiazoline-6-sulfonic acid (ABTS) in LML only, were found. Lysine increased milk's FRAP values and MDA content. Both L and HML diets increased milk's protein carbonyls content. Methionine improves the organism's oxidative status, without adversely affecting milk's oxidative stability. Lysine dietary inclusion affects negatively the oxidative stability of milk.